Boom not bust: Cooperative management as a mechanism for improving the commercial efficiency and environmental outcomes of regional scallop fisheries. (October 2021) - Bloor, Isobel S.M.; Duncan, Peter F.; Dignan, Samuel P.; Emmerson, Jack; Beard, David; Gell, Fiona R.; McHarg, Karen; Kaiser, Michel J.
Abstract: The environmental impacts of food production are increasingly influencing consumer's food choices. To maintain market access in this context, the fishing industry must adopt strategies and technologies that reduce their carbon emissions, environmental footprint, bycatch and seabed impact. In this study, closure of a depleted scallop fishing ground, to enable stock recovery, coupled with a transition to a cooperative management system, based on territorial user rights, promoted fishers to make management decisions that have improved the environmental outcomes and economic efficiency of this fishery. Innovative cooperative management systems like territorial user rights that decentralise decision making and provide users rights to a defined fishing area, could help mitigate against the negative impacts and issues traditionally associated with scallop dredge fisheries, and help maintain both stock biomass and consumer demand in a market increasingly dominated by sustainably certified food products.